Impact of Displacement on Civil and Political Rights of the Internally Displaced Persons in Dolakha District of Nepal - Karki, Netra Bahadur (Journal of APF Command and Staff College, 2019)
The explanatory paper discusses the impact of displacement on the civil and political rights of the internally displaced persons (IDPs) in Dolakha District of Nepal with special reference to the displacement caused by the 2015 Nepal Earthquake. The discussion has focused on studying the answer for whether the disaster-induced IDPs enjoyed the civil and political rights particularly during the Federal, Provincial and Local elections in Nepal. The findings are based on the primary data collected from the respondents, IDPs and the people’s representatives, who are the key aspect of the real time empirical familiarity, and of course supported by secondary data. The main issue in the paper is whether the IDPs could enjoy the civil and political rights during the tri-phases of election in 2017 in Dolakha District of Nepal, and the claim is that some of the civil and political rights of the IDPs were unconstructively impacted because of their status of being displaced.